Characterization of the Interactions of the Bacterial Cell Division Regulator MinE - Hafizi, Fatima (Université d'Ottawa / University of Ottawa, 2012)
Symmetric cell division in gram-negative bacteria is essential for generating two equal-sized daughter cells, each containing cellular material crucial for growth and future replication. The Min system, comprised of proteins MinC, MinD and MinE, is particularly important for this process since its deletion leads to minicells incapable of further replication. This thesis focuses on the interactions involving MinE that are important for allowing cell division at the mid-cell and for directing the dynamic localization of MinD that is observed in vivo. Previous experiments have shown that the MinE protein contains an N-terminal region that is required to stimulate MinD-catalyzed ATP hydrolysis in the Min protein interaction cycle. However, MinD-binding residues in MinE identified by in vitro MinD ATPase assays were subsequently found to be buried in the hydrophobic dimeric interface in the MinE structure, raising the possibility that these residues are not directly involved in the interaction. To address this issue, the ability of N-terminal MinE peptides to stimulate MinD activity was studied to determine the role of these residues in MinD activation. Our results implied that MinE likely undergoes a change in conformation or oligomerization state before binding MinD. In addition we performed circular dichroism spectroscopy of MinE. The data suggest that direct interactions between MinE and the lipid membrane can lead to conformational changes in MinE. Using NMR spectroscopy in an attempt to observe this structure change, different membrane-mimetic environments were tested. However the results strongly suggest that structural studies on the membrane-bound state of MinE will pose significant challenges. Taken together, the results in this thesis open the door for further exploration of the interactions involving MinE in order to gain a better understanding of the dynamic localization patterns formed by these proteins in vivo.
Keywords: cell division; MinE; MinD; mitosis; NMR; CD; HSQC; lipids; membrane binding; Hill Equation; detergents; bicelles; micelles; ATPase activity; binding affinity; peptide; FtsZ; kinetics; cooperativity